2015
DOI: 10.7763/ijiet.2015.v5.573
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Online Learning in an Australian University: Malaysian Students’ Perspective – Support for Learning

Abstract: Abstract-Several researchers have reported that cultural and language differences can affect online interactions and communications between students from different cultural backgrounds. Other researchers have asserted that online learning is a tool that can improve teaching and learning skills, but its effectiveness depends on how the tool is used. To delve into these aspects further, this study set out to investigate the kinds of learning difficulties encountered by the international Asian students, in partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 20 publications
2
31
1
3
Order By: Relevance
“…For example, research at the turn of the century indicated differences between Australians and Asian students in student perceptions (Smith & Smith, 1999;Ramburuth & McCormick, 2001); however, a more recent study found no significant differences existed on many factors for these groups (Chew & Yee, 2015). Yet, another study reported on changes in Chinese students' motivation and learning strategies after an online collaborative experience towards a social-constructivist learning approach (Zhu et al, 2009).…”
Section: What Do We Know About Cultural Perceptions About Online Educmentioning
confidence: 95%
See 3 more Smart Citations
“…For example, research at the turn of the century indicated differences between Australians and Asian students in student perceptions (Smith & Smith, 1999;Ramburuth & McCormick, 2001); however, a more recent study found no significant differences existed on many factors for these groups (Chew & Yee, 2015). Yet, another study reported on changes in Chinese students' motivation and learning strategies after an online collaborative experience towards a social-constructivist learning approach (Zhu et al, 2009).…”
Section: What Do We Know About Cultural Perceptions About Online Educmentioning
confidence: 95%
“…Mixed results in cross-cultural comparisons exist for many program characteristics; however, recent research appears to indicate that the Millennials generation regard online education differently and are more accepting than Gen-Xers or Gen-Yers (Chew & Yee, 2015). Additionally, several studies note that students' perceptions changed over time (Benbunan-Fich & Hiltz, 203;Karns, 2005;Mortagy & Boghikian-Whitby, 2010;Perreault et al, 2008;Ramburuth & McCormick, 2001;Smith & Smith, 1999;Zhu et al, 2009) Previous research demonstrates mixed student perceptions of online education that differed in facility size (small, medium, and large universities), audience (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, studies have revealed that culture also had influence on an individual's needs, preferences and expectations towards education [6][7][8]. For example, Western learners expect constructivist learning approach in contrast to Eastern learners, thus Western learners prefer to utilize social constructivist tool such as e-learning, Wikipedia and Facebook [6,9,10].…”
Section: Introductionmentioning
confidence: 99%